Celebrification of Instagram Users As a Practice - Yeru, Tanya Eirena (KnE Social Sciences, 2019)
This paper discusses celebrification that occurs on social media, especially Instagram. Celebrification on Instagram triggered the emergence of the Instagram famous phenomenon called ‘Instagram celebrity’. Instagram celebrity itself is a term that is used among users in Indonesia. It is a status given to Instagram users who earn and increase online popularity through and on Instagram. In fact, celebrification on Instagram is different from the celebrification that occurs in conventional mass media. Therefore, using Bourdieu’s concept of habitus and ethnographic method, this paper focuses on the practice of celebrification by Instagram users who make themselves an Instagram celebrity. Research was conducted by participant observation and interviews with three informants who are Instagram celebrities based in Yogyakarta, there are two main findings: (1) Instagram celebrities are active and creative users so that the practice of celebrification in Instagram can be seen as a result of participatory habitus, and (2) participatory habitus can be conceptualized as a strategy to challenge the traditional ways in celebrity production, including the mediagenic persona and performance of authenticity. Keywords: practice, celebrification, celebrity, Instagram, users, participatory, habitus